PENGEMBANGAN KETERAMPILAN KOMUNIKASI GURU UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN - Robi’ah, Robi’ah; Lukman, Lukman; Fadli, M Khairul (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Teachers are the most crucial element in the overall structure of the education system, which should be the main and central focus. . Teachers have a key role in the development of education, especially in the context of formal implementation in the school environment. lack of time management skills. Therefore, all improvement efforts to improve the quality of education will not have a significant impact without the support of teachers who have good professionalism and qualifications. In this study using descriptive qualitative research methods using library research methods. Researchers in this case as the core instrument assisted by incidental tools conduct studies and analysis of scientific literature in the form of books, scientific journal articles and other scientific papers related to Teacher Communication Skills Determine Learning Effectiveness. Teachers’ communication skills have a crucial role in determining the effectiveness of learning. Camp